Potential Oil Palm Industry Development in Riau - Syahza, Almasdi; Rosnita, Rosnita; Suwondo, Suwondo; Nasrul, Besri (International Research Journal of Business Studies, 2013)
Oil palm is one of Indonesia’s main commodities that play a role in the growth of the national economy. It has a considerable contribution in generating foreign exchange and employment. Development of Indonesia’s CPO processing industry and its derivatives is in line with the growth of plantation area and production of oil palm as a source of raw materials. Until 2011, Indonesia’s oil palm plantation area reached 2,103,175 ha with an FFB production of 36,809,252 tons. Meanwhile, oil palm mill (OPM) processing capacity was 30,019,200 tons only. The analysis showed the regional carrying capacity (RCC) was 1.584. Each FFB should be processed in less than 8 hours or RCC for OPM must be smaller than 1 (RCC, 1). Higher production of oil palm plantations in Riau is the potency to increase the OPM. The results of calculations by land development and farm productivity, Riau region is still lacking of 16 OPM units with a capacity of 60 tons / hour or identical to 21 OPM units at a capacity of 45 tons / hour. The deficiency in OPM impacts the price and income of oil palm farmers in rural areas. High demand for OPM in Riau is a business opportunity for investors to develop an OPM and industry of products derived from oil palm.